2020
DOI: 10.1101/2020.12.17.423095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A MYT1L Syndrome mouse model recapitulates patient phenotypes and reveals altered brain development due to disrupted neuronal maturation

Abstract: Human genetics have defined a new autism-associated syndrome caused by loss-of-function mutations in MYT1L, a transcription factor known for enabling fibroblast-to-neuron conversions. However, how MYT1L mutation causes autism, ADHD, intellectual disability, obesity, and brain anomalies is unknown. Here, we develop a mouse model of this syndrome. Physically, Myt1l haploinsufficiency causes obesity, white-matter thinning, and microcephaly in the mice, mimicking clinical phenotypes. Studies during brain developme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…However, a MYT1 proteomics study with Neuro2A cell identified LSD1-CoREST-PHF21A complex (48), which is consistent with our results and suggests plausible roles of the complex in the MYT-mediated transcriptional regulation of neurodevelopmental gene expression program. Furthermore, MYT1L can also activate the transcription of neuronal maturation genes with unknown mechanisms (25,49). It is tempting to speculate that the neuronal splicing of LSD1 and PHF21A is responsible for the functional switch of MYT1L from repressor to activator, with the neuronal LSD1-PHF21A complex acting as a dominant negative machinery.…”
Section: Discussionmentioning
confidence: 99%
“…However, a MYT1 proteomics study with Neuro2A cell identified LSD1-CoREST-PHF21A complex (48), which is consistent with our results and suggests plausible roles of the complex in the MYT-mediated transcriptional regulation of neurodevelopmental gene expression program. Furthermore, MYT1L can also activate the transcription of neuronal maturation genes with unknown mechanisms (25,49). It is tempting to speculate that the neuronal splicing of LSD1 and PHF21A is responsible for the functional switch of MYT1L from repressor to activator, with the neuronal LSD1-PHF21A complex acting as a dominant negative machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The open field test was used to assess the general activity and approach/avoidance (anxiety-like) behaviors of mice at P40 over a 1-hour period, based on previously published methods 12,13 . The test was performed using a transparent, acrylic testing apparatus (50×50×50 cm) enclosed within a white sound-attenuating box with dim red lighting at 10 lux.…”
Section: Open Field Testmentioning
confidence: 99%
“…Social motivation, including social reward seeking and social orienting was evaluated from P83-P98 using a social operant task. Procedures used here were as described previously 12 (Fig. S2C) with minor alterations.…”
Section: Social Operantmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of FTSJ1 in humans gives rise to ID, yet the underlying mechanism is still unclear. Both neuronal morphology 76 and behaviour 27 have been reported in patients affected by a wide range of ID disorders, with a variety of genetic etiologies and their corresponding mouse models. To address whether loss of human FTSJ1 also affects neuronal morphology, we altered FTSJ1 activity using 2,6-Diaminopurine (DAP) 77,78 in human Neural Progenitor Cells (NPC).…”
Section: Ftsj1 Is Involved In Human Neuronal Morphology During Developmentmentioning
confidence: 99%